ANALISIS SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA DI RUMAH SAKIT: SEBUAH TINJAUAN LITERATUR (Faletehan Jurnal Ekonomi dan Bisnis, 2023)
ABSTRACT This study aims to analyze the Hospital Occupational Health and Safety Management System in Hospital. This study uses a descriptive with qualitative method. The results of the study indicate that the implementation of SMK3 in hospitals has not gone well based on the Regulation of the Minister of Health of the Republic of Indonesia Number 66 of 2016. The obstacles faced by hospitals include a policy commitment by top management, organizational formation (P2K3) constrained by competent human resources. The preparation of K3RS planning is not in accordance with risk management. Implementation, monitoring and evaluation have not run effectively, weak supervision, enforcement of regulations, and inadequate budgetary support, infrastructure and facilities, including weak of safety culture. A joint commitment effort is needed, supported by effective resources for the implementation of a sustainable SMK3 in hospitals. Keywords: SMK3, P2K3, Hospital